Impact of Leadership Qualities on Employee Commitment in Multi-Project-Based Organizations - M., Waris; Asadullah, Khan; Ishak, Ismail; Adeleke, A. Q.; Panigrahi, Shrikant (IOP Publishing, 2018)
The purpose of this study is to investigate the impact of multiple leadership qualities on employee commitment in multi-project-based organizsations. The dimensions of leadership qualities develop a healthy organizational environment which will lead to job satisfaction and, ultimately, job commitment. Multiple leadership qualities inspire the subordinates, as collective in nature, to get extra ordinary goals in the hyper competitive era. The main objective of this research is two fold ; firstly, to find out the impact of multiple leadership qualities on employee job affectiveness and calculative commitment and secondly, to investigate the extent of the impact of multiple leadership qualities on organizations. A total of 213 respondents were included in the study from different organizations. The data were analyzed through regression analysis by using the SPSS. The finding shows that all of the variables have a positive correlation with each other. The correlation of multiple leadership qualities and employee job commitment was also found to be significant, which shows that multiple leadership qualities have an impact on the organizations. Conceptual framework of the study is developed as Multiple Leadership Qualities an independent variables and its impact has been examined on the Employee Job Commitment. The results supported the hypothesis that multiple leadership qualities have a positive and significant impact on employee job commitment.